2005
DOI: 10.1038/sj.onc.1209192
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion and prostate tumor-suppressor activity of TSLL2/IGSF4C, an immunoglobulin superfamily molecule homologous to TSLC1/IGSF4

Abstract: The TSLL2/IGSF4C encodes an immunoglobulin (Ig) superfamily molecule showing significant homology with a lung tumor suppressor, TSLC1. The TSLL2 protein of 55 kDa is mainly expressed in the kidney, bladder, and prostate in addition to the brain. Here, we report the biological significance of TSLL2 in the urinary tissues. An immunohistochemical study reveals that TSLL2 is expressed at the cell-cell attachment sites in the renal tubules, the transitional epithelia of the bladder, and the glandular epithelia of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 26 publications
3
55
0
Order By: Relevance
“…As the positive control, we found that TSLC1 expression was high in normal bladder tissue and the expression was restricted to urothelial cells (fig. 1d), consistent with previous report [26]. …”
Section: Resultssupporting
confidence: 83%
“…As the positive control, we found that TSLC1 expression was high in normal bladder tissue and the expression was restricted to urothelial cells (fig. 1d), consistent with previous report [26]. …”
Section: Resultssupporting
confidence: 83%
“…9,10 We have reported that CADM4 is expressed in the brain, lung, large and small intestines and urinary organs and that CADM4 could act as a tumor suppressor in prostate cancer. 11 We have also demonstrated that CADM1 associates with an actin-binding protein, 4.1B/DAL-1, through the FERM-binding motif in the cytoplasmic domain. 12 Frequent loss of 4.1B in lung adenocarcinoma, breast cancer and meningioma suggested that 4.1B could be a tumor suppressor.…”
mentioning
confidence: 99%
“…11 The CADM1 antibodies used in this study were two rabbit polyclonal antibodies (pAbs) against the cytoplasmic domain, C-18, 22 and number 6 and a chicken monoclonal antibody (mAb) against the ectodomain, 3E1. 23 A rabbit pAb against 4.1B/DAL-1 was described previously.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…IGSF4 encodes a transmembrane protein whose extracellular domain shows close homology to the immunoglobulin superfamily cell adhesion molecules (Ig-CAM), particularly with the neural cell adhesion molecules, N-CAM1 and N-CAM2, 10 and the prostate tumor-suppressor TSLL2/IGSF4C. 11 Silencing of IGSF4, 12 is frequently observed in solid tumors including lung, 13 prostate, 10 pancreatic, gastric, breast, nasopharyngeal, 14 and cervical cancers, 15,16 as well as nasal NK/T-cell lymphoma. 17 Restoration of IGSF4 expression decreases epithelial cell scattering and tubulogenesis and suppresses lung cancer metastasis in nude mice, 13,18 -20 IGSF4 also reduces the anchorage-independent growth and tumorigenicity of cervical cancer cells.…”
mentioning
confidence: 99%